Low-resistivity vertical current transport across AlInN/GaN interfaces. (21st December 2020) - Sana, Prabha; Seneza, Cleophace; Berger, Christoph; Witte, Hartmut; Schmidt, Marc-Peter; Bläsing, Jürgen; Neugebauer, Silvio; Hoerich, Florian; Dadgar, Armin; Strittmatter, André
Abstract: Effects of n-type doping of Al0.82 In0.18 N/GaN heterostructures on the conduction band (CB) profile have been investigated. Doping concentrations well above 10 19 cm −3 are required to reduce the large barriers in the CB. Experimentally, Si- and Ge donor species are compared for n-type doping during metalorganic vapor phase epitaxy. For Si doping, we find substantial interface resistivity that will strongly contribute to total device resistivity. Doping of AlInN is limited by either the onset of a self-compensation mechanism (Si) or structural degradation of the AlInN (Ge). Only by Ge doping, purely ohmic behavior of periodic AlInN/GaN layer stacks could be realized.